2017
DOI: 10.12659/msm.901003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Weight Loss, Ghrelin, and Leptin Hormones After Ligation of Left Gastric Artery and Sleeve Gastrectomy in a Rat Model

Abstract: BackgroundLigation of the left gastric artery (LLGA), which supplies the fundus of the stomach, may reduce the appetite hormone ghrelin, resulting in weight control. The aim of this study was to compare LLGA and sleeve gastrectomy (SG) in terms of postoperative outcomes in a rat model.Material/MethodsFifteen male Wistar albino rats, weighing >350 grams (range 350–525 grams), were enrolled in LLGA (N=5), SG (N=5), and control (N=5) groups. Blood samples were drawn preoperatively and also during the first and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The possible reason was that LSG, as a restrictive operation, also removed the gastric fundus, which would reduce the secretion of Ghrelin. Ghrelin secreted at the gastric fundus promoted appetite and decreased the secretion of insulin and enhanced insulin resistance (23,24). Therefore, inhibition of secretion of Ghrelin could also treat the diabetes and obesity (25).…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason was that LSG, as a restrictive operation, also removed the gastric fundus, which would reduce the secretion of Ghrelin. Ghrelin secreted at the gastric fundus promoted appetite and decreased the secretion of insulin and enhanced insulin resistance (23,24). Therefore, inhibition of secretion of Ghrelin could also treat the diabetes and obesity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, sleeve gastrectomy decreased the leptin and ghrelin levels (13)(14)(15). Plasma ghrelin levels usually had increased in body mass index (16).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, leptin increases the oxidation and absorption of glucose and free fatty acid in skeletal muscles, as well as promotes intrahepatic lipid reduction through fatty acid oxidation ( 77 ). The changes in leptin levels after GAE are inconsistent ( 30 32 , 37 , 40 ), and its relationship with weight loss has not been investigated.…”
Section: Discussion: Influencing Factors For Efficacymentioning
confidence: 99%
“…Therefore, both animal and human studies have shown a decrease in ghrelin release from gastric fundic cells and an increase in GLP-1 and PYY which associated with reduced hunger and weight loss, and there was a positive correlation between weight loss and ghrelin, suggesting GAE may induce weight loss by lowering ghrelin. Yardimci et al ( 32 ) found that SG can lead to more significant weight loss by altering the anatomy of the gastrointestinal tract compared with GAE although ghrelin decrease similarly in the two procedures. This suggests that GAE is not as effective as conventional metabolic surgery, with the latter causing the most significant weight loss due to alterations in the anatomy of the gastrointestinal tract, with changes in gastrointestinal hormone levels being a secondary factor.…”
Section: Discussion: Influencing Factors For Efficacymentioning
confidence: 99%